The Distinction between Philosophy and the kata philosophian logos in Stoicism - Ponce Pérez, José Luis (Revista Archai, 2023)
This article answer what could be the distinction that the Stoics established between philosophy and the kata philosophian logos, according to the report by D.L., VII, 39-41. In this place I distance from the scholars who consider that the distinction is ontological, this is, that the kata philosophian logos refers to the discursive presentation of Stoic dogmas, whose nature is incorporeal, while the philosophy refers to a disposition of the soul, whose nature is corporeal. I rather propose that both are dispositiones or states of the rational part of the soul and that the difference is in the degree of perfection that they have accomplished.